Exchange rate pass-through to import prices in Europe: a panel cointegration approach - Antonia Arsova (Empirical Economics, 2020)
This paper takes a panel cointegration approach to the estimation of short- and long-run exchange rate pass-through (ERPT) to import prices in the European countries. Although economic theory suggests a long-run relationship between import prices and exchange rate, in recent empirical studies its existence has either been overlooked or it has proven difficult to establish. Resorting to novel tests for panel cointegration, we find support for the equilibrium relationship hypothesis. Exchange rate pass-through elasticities, estimated by two different techniques for cointegrated panel regressions, give insight into the most recent development of the ERPT.
Keywords: C12; C23; F31; 330; Exchange rate pass-through; Import prices; Panel cointegration; Cross-sectional dependence; Common factors